2015
DOI: 10.1074/jbc.m114.613091
|View full text |Cite
|
Sign up to set email alerts
|

Role of Small Subunit in Mediating Assembly of Red-type Form I Rubisco

Abstract: Background: Rubisco, a key photosynthetic enzyme of eight large and eight small subunits, is phylogenetically divided into green and red types. Results: The small subunits of red-type Rubisco contain a C-terminal ␤-hairpin extension that mediates efficient assembly of the holoenzyme. Conclusion: The C-terminal ␤-hairpin renders red-type Rubisco independent of specialized assembly chaperones. Significance: These findings can help in bioengineering red-type Rubisco into crop plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 46 publications
0
53
0
Order By: Relevance
“…Another sub- stitution, T418A (Chlamydomonas RbcL numbering), which replaces the indole side-chain of Trp-418 with the smaller methyl side-chain of alanine, could eliminate its van der Waals contact with small subunit Leu-6, although, in the Chlamydomonas structure, Ala-418 is in contact with small subunit Trp-4. However, large-small subunit interactions are quite robust and malleable, evidenced from the myriad of engineered hybrid enzymes with evolutionarily distant large-small subunits that have been expressed in higher plants, algae and bacteria (van der Vies et al, 1986;Kanevski et al, 1999;Wang et al, 2001;Sharwood et al, 2008;Genkov et al, 2010;Ishikawa et al, 2011;Joshi et al, 2015). Similarly, we discovered that Chlamydomonas RbcS can assemble with Synechococcus RbcL in E. coli to form hexadecameric holoenzyme (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…Another sub- stitution, T418A (Chlamydomonas RbcL numbering), which replaces the indole side-chain of Trp-418 with the smaller methyl side-chain of alanine, could eliminate its van der Waals contact with small subunit Leu-6, although, in the Chlamydomonas structure, Ala-418 is in contact with small subunit Trp-4. However, large-small subunit interactions are quite robust and malleable, evidenced from the myriad of engineered hybrid enzymes with evolutionarily distant large-small subunits that have been expressed in higher plants, algae and bacteria (van der Vies et al, 1986;Kanevski et al, 1999;Wang et al, 2001;Sharwood et al, 2008;Genkov et al, 2010;Ishikawa et al, 2011;Joshi et al, 2015). Similarly, we discovered that Chlamydomonas RbcS can assemble with Synechococcus RbcL in E. coli to form hexadecameric holoenzyme (data not shown).…”
Section: Discussionmentioning
confidence: 90%
“…In a recent study, co‐expression of the large subunit and RAF1 from Arabidopsis in tobacco chloroplasts has shown that Rubisco from higher plants prefers native RAF1 for efficient assembly (Whitney et al., ). On the other hand, the red‐type Rubisco from Rhodobacter sphaeroides was able to assemble in E. coli in the absence of extra assembly factors, and evidence indicated that a C‐terminal extension in its small subunit plays a similar role as RBCX to achieve the efficient assembly of the L 8 S 8 complex (Joshi et al., ). As a similar C‐terminal extension is also present in the small subunit of Griffithsia monilis (), its Rubisco might also be able to assemble in a heterologous environment in a similar manner.…”
Section: Discussionmentioning
confidence: 99%
“…Those findings indicated that the folding and assembly requirements of cyanobacterial Rubisco are not as strict as the Rubisco from higher plants and can be readily met in tobacco. An extra C‐terminal extension on the small subunit of the red‐type Rubisco from Rhodobacter sphaeroides has recently been observed to mimic the role of assembly factors, RBCX and RAF1, which were absent in organisms with red‐type Rubisco, suggesting that red‐type Rubisco may not require specific assembly factors (Joshi, Mueller‐Cajar, Tsai, Hartl, & Hayer‐Hartl, ). Therefore, we decided to reassess the expression of red‐type Rubisco in higher plants.…”
Section: Introductionmentioning
confidence: 99%
“…This b-subunit is then on standby until the unfolded freshly synthesized nuclear-encoded a-subunits are translocated across five membranes [18] to bind to the bsubunit in the stroma, thereby triggering the folding of the asubunit and the subsequent formation of the quaternary structure.T his scenario bears some resemblance to the assembly of Ribulose-1,5-bisphosphate carboxylate/oxygenase (Rubisco), whereby chaperones fold and then keep the plastid-encoded Rubisco large subunits (RbcL) from aggregating until the Rubisco small subunit (RbcS) becomes available. [23][24][25] This study has potential to inspire improvements in biotechnology methods for making quaternary protein complexes in vitro,a nd additionally in understanding ultrafast light-harvesting and protein folding in the quantum and chemical biology fields,respectively.Based on the mechanism proposed here,itshould be possible to design and synthesize novel hybrid quaternary light-harvesting protein complexes through complementary (cooperative) interactions between otherwise unrelated subunits.T he lessons learned here could be extended to synthetic (macro)molecular systems guiding the construction of complex multimeric (quaternary) foldamers. [26] Overall, our results suggest that subunit self-chaperoning [10,11] is important for the folding of the cryptophyte lightharvesting complexes,and may be awidespread feature of the folding of heteromeric protein complexes.…”
Section: Angewandte Chemiementioning
confidence: 99%